Detection of Vehicle Parking Space Using Image Processing in Matlab - G. Sai Sravanthi, P. Prakash, K. Latha, M. Madhubabu (Mathematical Statistician and Engineering Applications, 2021)
An intelligent parking spot recognition system based on image processing technology is what this research intends to propose. The suggested system takes a round picture drawn on a parking area, processes it, and outputs data about the available parking spots for cars.In this project, a camera serves as a sensor to take pictures that display how full parking lots are. A camera is utilised because it can detect the presence of multiple cars simultaneously using an image.To detect various car parking lots, the camera may also be conveniently moved. With the use of this image, it is possible to identify which parking lots are empty, and the processed data is then utilised to direct drivers to vacant lots rather than making them search for them.The suggested system has been created on a hardware and software platform. For both drivers and administrators, an autonomous parking system is employed to simplify and increase the efficiency of the entire parking process.